Forage utilisation in smallholder systems - African and SE Asian perspectives - Roothaert, Ralph L. (International Livestock Research Institute, 2005)
-some facts and numbers -how are forages used in smallholder systems in Africa and Asia? empirical evidence of benefits from forages -what are the smallholder challenges? -what are our R4D challenges?